General decay for a class of viscoelastic problem with not necessarily decreasing kernel. Issue 9 (4th July 2019) - Ouchenane, Djamel; Boulaaras, Salah; Mesloub, Fatiha
ABSTRACT: In this paper, a problem which arises in a class of viscoelasticity is considered. We obtain the decay rate of the energy, for certain class of relaxation functions not necessarily exponentially or polynomially decaying to zero.